PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR) DAN BOPO TERHADAP PROFITABILITAS (ROA DAN ROE) BANK PERSERO INDONESIA YANG DIPUBLIKASIKAN BANK INDONESIA PERIODE 2010 – 2015 - Hani Maulida Khoirunnisa; Rodhiyah Rodhiyah; Saryadi Saryadi (Universitas Diponegoro, 2016)
State-owned banks have involvement with many parties in their business, so the performance maintenance is benecessary to deal with banking risks that may arise. The downward trend in the profitability of state-ownedbanks indicated by Return on Assets (ROA) and Return on Equity (ROE) becomes a problem when the CapitalAdequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and ROA experiencing upward trend.The purpose of this study was to determine the effect of CAR, LDR and ROA on ROA and ROE withexplanatory method. The study population was a quarterly financial report of four state banks in Indonesia2010-2015 so that the number of samples obtained as many as 96 by using purposive sampling. Data analysistechnique used is the classical assumption test, linear regression test, and the test of significance using SPSS15.0 software application.Results and discussion: CAR significant positive effect on ROA of 5.5%, LDR significant negative effecton ROA of 28.6%, and ROA significant negative effect on ROA of 68.8%. CAR, LDR, and ROA significantpositive effect on ROA 69.5%. CAR does not affect the ROE, LDR significant negative effect on ROE of 31%,and ROA significant negative effect on ROE of 48.5%. CAR, LDR, and ROA significant positive effect on ROEof 50.9%.Conclusions and suggestions: CAR, LDR and BOPO positive effect on profitability (ROA and ROE).State-owned banks are expected to increase liquidity and operational efficiency by reducing the percentage ofLDR and ROA.